A Randomized Controlled Trial of Opt‐in Versus Opt‐Out Colorectal Cancer Screening Outreach. (December 2018) - Mehta, Shivan J.; Khan, Tanya; Guerra, Carmen; Reitz, Catherine; McAuliffe, Timothy; Volpp, Kevin G.; Asch, David A.; Doubeni, Chyke A.
Abstract : OBJECTIVES: Colorectal cancer (CRC) screening uptake is suboptimal, despite national efforts to increase screening rates. Behavioral economic approaches such as changing defaults may increase participation. We compare response rates to opt‐in or opt‐out messaging in mailed fecal immunochemical test (FIT) outreach. METHODS: This is a two‐arm randomized controlled trial among 314 patients aged 50‐74 years who had at least two primary care visits in the 2‐year pre‐enrollment period and were screening‐eligible but not up‐to‐date. Eligible patients received invitation by electronic health record (EHR) portal or mail with randomization to receive mailed FIT: (1) only if they actively opted‐in to do so (opt‐in) or (2) unless they opted‐out of screening (opt‐out). The primary outcome was FIT completion rate within 3 months of initial outreach. RESULTS: Patients randomized to opt‐in agreed to participate 23.1% of the time, and only 2.5% of those in opt‐out chose not to participate. FIT kits were mailed to 22.4% and 93% of patients in opt‐in and opt‐out arms, respectively. In intention‐to‐screen analysis, patients in the opt‐out arm had a higher FIT completion rate (29.1%) than in the opt‐in arm (9.6%) (absolute difference 19.5%; 95% confidence interval, 10.9‐27.9%; P < .001). Results were similar in subgroup analysis of those sent initial messaging through the EHR portal (9.5% opt‐in versus 37.5% in opt‐out). CONCLUSIONS: Mailed CRC screening outreach providing an option to opt‐out had significantly higher participation rates than opt‐in messaging. Opt‐out messaging approaches can boost participation in population health outreach efforts.